2008
DOI: 10.1007/s10620-007-0183-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Oral l-Acyl-Carnitine an Effective Therapy for Hepatic Encephalopathy? Review of the Literature

Abstract: Hepatic encephalopathy (HE) is a significant cause of morbidity and mortality in patients with advanced chronic liver disease. Current therapies are associated with inconvenient side-effects, high cost, and incomplete efficacy. The quanternary ammonium compound L-acyl-carnitine has been suggested as a potent, low-cost, and safe alternative therapy for patients with cirrhosis and HE. A systematic review of the literature assessing the use of carnitine in the treatment of HE identified three high-quality human t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…L-acyl-carnitine has been suggested as a potent, low-cost, and safe alternative therapy for patients with cirrhosis [58]. Minimal hepatic encephalopathy (MHE) is a serious and common complication that occurs in the majority of cirrhotic patients [59].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…L-acyl-carnitine has been suggested as a potent, low-cost, and safe alternative therapy for patients with cirrhosis [58]. Minimal hepatic encephalopathy (MHE) is a serious and common complication that occurs in the majority of cirrhotic patients [59].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic encephalopathy (HE) is a significant cause of morbidity and mortality in advanced cirrhotic patients [58]. Although the mechanisms by which carnitine provides neurological protection are unknown, a systematic review of the literature confirmed that L-acyl-carnitine is promising as a safe and effective treatment for HE [58].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include prevention of glutamate‐mediated neurotoxicity in N‐methyl‐D‐aspartate type glutamine receptors. A systematic review identified three high quality clinical trials assessing the efficacy of L‐carnitine in treating HE . These studies reported positive effects such as decreased serum ammonia concentrations and improved neuropsychological test scores in comparison to accepted therapies.…”
Section: Current Published Human Researchmentioning
confidence: 99%
“…10,11,15 Additionally, since ALC acts as a direct antioxidant, ALC supplementation has been shown to be effective in inhibiting oxidative stress and death in rat models of dementia and chronic ischemia. [16][17][18][19] However, in the clinical studies in LC patients with MHE or OHE-except for a report by Saito et al…”
Section: Introductionmentioning
confidence: 99%